(untitled) (Fiep Bulletin - online, 2015)
The so-called dislipedemias have been appointed as a factor causing chronic degenerative diseases as Coronarian Arterial Disease (CAD) and other aterosclerotic diseases. Hypercholesterolemia is a kind of dislipidemia characterized by a high concentration of LDL serum cholesterol, causing aterogenesis and increasing the risk of CAD. Physical activity has been demonstrated to act beneficially on the factors leading to chronic degenerative diseases and having its effect potentialized when combined with a balanced diet. In the present work 48 female Fisher adult rats were distributed into four groups: Execice (swimming 30 min/day, 5 days/week) with Hypercholesterolemic Diet, Exercice with Control Diet, Sedentary with Hypercholesterolemic Diet and Sedentary with Control Diet. After 9 weeks the animals were sacrificed. The obtained results show that exercice was efficient in reducing total cholesterol, influenced in the wheight of soleo muscle and there was indication of effect on the oxidative stress as shown by increase in the concentration of free sulphydril groups and reduction of paraoxonase activity. The results indicate that low intensity training is capable of altering positively the cholesterol profile and suggest that new studies be made with different volumes and intensities of training.